(untitled) (Research, Society and Development, 2025)
Basil (Ocimum basilicum L.) is an aromatic and medicinal species of great economic importance, widely used in the culinary, pharmaceutical, and cosmetic sectors. The physiological quality of seeds is crucial for seedling establishment and for the productive success of the crop, with vigor tests serving as essential tools for selecting seed lots with superior performance. Therefore, this study aimed to identify the most efficient vigor tests for assessing the physiological potential of basil seeds. The experiment followed a completely randomized design with four replications, using five seed lots of the cultivar Basilicão, supplied by Isla Sementes®. The lots were evaluated through germination tests (first count and final percentage), accelerated aging (traditional and with saline solution), electrical conductivity, seedling length, and seedling emergence at seven and fourteen days after sowing. The results revealed significant differences among seed lots in most tests, except for electrical conductivity and first germination count. The outcomes of the vigor tests were consistent with the seedling emergence results, with seedling length and both traditional and saline-solution accelerated aging tests showing greater accuracy in differentiating seed lots in terms of vigor. It is concluded that the traditional and saline-solution accelerated aging tests, along with seedling length evaluation, are effective for assessing the vigor of basil seed lots.